Die Kinder des Schweigens Familie, Verwandtschaft und Heirat bei den Arvaniten im südöstlichen Attika (1850-1940) - Alexakis, Eleftherios P. (2008)
The original edition "Ta paidia tis siopis" was published by Ekdoseis Parousia Publishing House (ISBN 960-7601-64-5). The author owns the copyright and transferred it to the editor of the German translation for free. The author is one of the most prominent ethnologists of Greece. He investigates the family and kinship structures as well as the marriage practices, the transfer of marriage goods, and the dowry stystem of in the Arvanite villages in Southeastern Attica (Southern Greece) on the basis of fieldwork and archival research. The Arvanites represent the predecessors of the present Albanian population a branch of which migrated to its present settlements in the second half of the 14th century. The main title of the book is related to the fact that due to the adaption processes of th 19th and 20th centuries this ethnic group does not any longer practice its original language in everyday life. The author states that also the original social structure shifted towards the Greek environment, e.g. in form of ambilineal descent calculation instead of the original patrilineal descent calculation. Alexakis work enters scientific newland insofar as the author is the first Greek scholar who treats this topic from a modern historical-anthropological perspective. He, therefore, sheds ligtht on a topic that had been ignored by official Greece until a few years ago. The book is structured into three chapters: 1) Marriage Payments 2) Familiy and Property Transfer 3)Ambilineal Descent Group and Marriage Strategies.